3x+7-5(x-1)=5x+4

Simple and best practice solution for 3x+7-5(x-1)=5x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+7-5(x-1)=5x+4 equation:


Simplifying
3x + 7 + -5(x + -1) = 5x + 4

Reorder the terms:
3x + 7 + -5(-1 + x) = 5x + 4
3x + 7 + (-1 * -5 + x * -5) = 5x + 4
3x + 7 + (5 + -5x) = 5x + 4

Reorder the terms:
7 + 5 + 3x + -5x = 5x + 4

Combine like terms: 7 + 5 = 12
12 + 3x + -5x = 5x + 4

Combine like terms: 3x + -5x = -2x
12 + -2x = 5x + 4

Reorder the terms:
12 + -2x = 4 + 5x

Solving
12 + -2x = 4 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
12 + -2x + -5x = 4 + 5x + -5x

Combine like terms: -2x + -5x = -7x
12 + -7x = 4 + 5x + -5x

Combine like terms: 5x + -5x = 0
12 + -7x = 4 + 0
12 + -7x = 4

Add '-12' to each side of the equation.
12 + -12 + -7x = 4 + -12

Combine like terms: 12 + -12 = 0
0 + -7x = 4 + -12
-7x = 4 + -12

Combine like terms: 4 + -12 = -8
-7x = -8

Divide each side by '-7'.
x = 1.142857143

Simplifying
x = 1.142857143

See similar equations:

| 8r+10y=48 | | 8x-9-6x+14=11x-9-10+13 | | -7.24=x/4+3 | | a*2/(4+6)=10 | | 15x^2+19m+6=0 | | -5x+15.8=3.3 | | 3-4(5-7)=z | | Z+6/8=Z-5/7 | | -3(3v-7)+7v=6+3(2v-1) | | -1.1+u/2=-13.9 | | 6=-19+t | | 7(x+4)=-3(x+2)+4 | | 5+2u=19 | | .3x+2=2.6 | | 25=-14+y | | -3+4(-2+7)= | | -24=w/4-4 | | (3)/(x^2-2x)-(2)/(x)=(8)/(x-2) | | 8+6v=6v-6+7v | | 3y-2+3(2y+1)=-3(y+3) | | 58=-x+171 | | y-(-9)=(-14/3)(x-(-9)) | | x/37+25=50 | | 7x+3=2x-17 | | 240=-w+30 | | (x+12)/(x-3)+1=(15)/(x-3) | | y-5=(-14/3)(x-(-6)) | | 77=(x/100)99 | | 1=2x-17 | | -5(v+1)=-4(2v-1)+9v | | 23=y/5+12 | | 2x-14=26 |

Equations solver categories